Numerical Simulation of the Effect of Stress on the Seepage of Fractured Rock Mass - Liang Shiwei; Wang Hongmei; Ge Di; Zhao Cunqing (Geofluids)
In our country, the Yellow River Basin ecological protection and development are put forward under the background of high quality. Among the 14 large-scale coal bases in our country, 9 coal bases are located in the Yellow River Basin, and the Shenfu-Dongsheng Coalfield, which is currently the largest under development, is located here. The region is in the process of coal mining, and the movement of overlying strata will cause the stress redistribution and coal seam in overlying aquifers also due to the effect of pore water pressure along the seepage of rock fracture and damage of overlying aquifer, so in the same formation, stress and the coupled action of seepage flow will produce mutual influence. This article through the early stage of the theoretical results discussed the application of numerical simulation method for simulating 2301 face, and the effect of stress on seepage is concluded. It is proved that the numerical simulation analysis has an important reference value for the coupling problem of stress and seepage. At the same time, the protective mining of aquifers is the basic condition for the surface ecological protection of the area, and it also provides a theoretical basis for the restoration of the ecological environment in the coal mining areas of the Yellow River Basin.